Porcine Reproductive and Respiratory Syndrome: A review of the etiological agent and its influence on the current behaviour of the disease - Castillo Espinoza, Ana (2021)
Porcine reproductive and respiratory syndrome (PRRS) is a worldwide viral disease that causes reproductive failure in adult pigs and respiratory problems in young animals. PRRS causes serious economic losses, which is why it is considered the infectious disease with the greatest economic impact affecting the world swine industry. Given the proven genetic variability of the virus, the International Committee on Taxonomy of Viruses (ICTV) has reclassified the genotypes initially recognized as European and American; renaming them Betaarterivirus suid-1 and 2, respectively. The reclassification would be widely influenced by the biology of the virus, which impacts on the use of diagnostic techniques, and on the implementation of the disease control and prevention mechanisms. The objective of this review is to provide the veterinary community with updated information on the recent taxonomic classification, the organization of the genome, the mechanisms of immune response and the economic impact in South America, as well as the new alternatives for the diagnosis, control and prevention of this Viral agent of great repercussion in the national swine industry.